(untitled) (GYMNASIUM, 2017)
In preparing this study went on the premise that the budget of the individual’s leisure time has gained new values in the context of the 21st century. We propose that this study to identify the sports activities in leisure time activities, on the one hand, and on the other hand, to identify the types of sporting activities (sports, namely branches) that social actors young people (students) prefer. The sample was made up of 100 subjects (54 male, 46 female gender), students of the University ’Al.I.Cuza’ of Iaşi, Faculty of Physical Education and Sport who were asked to fill in a questionnaire with 9 items. Expected results the survey undertaken highlight the, surprisingly, that daily main activities are using the computer, discussions with friends on the cell phone and watching TV programs. Leisure sport activities, individual and indoor, prevail when we refer to the allotted time per day. Weekly sports activities in nature takes up more time. Practicing sport leisure activities targe those activities which involve little cost.